2021
DOI: 10.3389/fpls.2021.729021
|View full text |Cite
|
Sign up to set email alerts
|

Super Rice With High Sink Activities Has Superior Adaptability to Low Filling Stage Temperature

Abstract: To investigate the differential responses of super rice grain filling to low filling stage temperature (LT) and the regulative effect of nitrogen panicle fertilizer (NPF), physiological and molecular experiments were conducted with two super rice varieties (Nanjing 7th: N7 and Nanjing 9108th: N9108) on two different filling stage temperature treatments implemented by applying two sowing dates [Normal filling stage temperature (CK): Sowed on May 30, Tmean = 24.7°C and low filling stage temperature (LT): Sowed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
2
5
0
Order By: Relevance
“…The reduction of these enzymatic activities leads to a decrease in the conversion of starch synthesis substrates and starch accumulation efficiency (Zhang et al, 2018). Additionally, LT also reduced the starch biosynthesis rate and starch content by down-regulating the expression of starch synthesis-related genes, thus inhibiting the grain filling rate (Xu et al, 2021). In this study, Pearson's correlation analysis further revealed that the enzymatic activities related to starch synthesis were positively correlated with starch content, starch accumulation, and dry matter accumulation in grain (Figure S1).…”
Section: Discussionsupporting
confidence: 52%
“…The reduction of these enzymatic activities leads to a decrease in the conversion of starch synthesis substrates and starch accumulation efficiency (Zhang et al, 2018). Additionally, LT also reduced the starch biosynthesis rate and starch content by down-regulating the expression of starch synthesis-related genes, thus inhibiting the grain filling rate (Xu et al, 2021). In this study, Pearson's correlation analysis further revealed that the enzymatic activities related to starch synthesis were positively correlated with starch content, starch accumulation, and dry matter accumulation in grain (Figure S1).…”
Section: Discussionsupporting
confidence: 52%
“…With higher translocation rates, the weights of superior and large grains on the primary branches are generally increased. In contrast, inferior and light grains positioned on the secondary branches generally have slow translocation rates; therefore, they are considered poorly filled grains and generally undesirable for human use (Xu et al, 2021). Similar observations have been observed in research reporting the significant effects of temperature, maximum grain-filling rate, and average grain-filling rate on grain quality in different climatic conditions (Tables 6, 7).…”
Section: Rice Quality In Inferior and Superior Grainssupporting
confidence: 77%
“…In addition to high temperatures, low temperatures at the filling stage also affect grain filling. Under low temperatures, grain filling is inhibited, mainly due to a reduced starch biosynthesis rate (Xu et al, 2021a).…”
Section: Four Other Factors Indirectly Influence Grain Fillingmentioning
confidence: 99%